2016
DOI: 10.1053/j.gastro.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Cause of Abdominal Pain

Abstract: Question: A 77-year-old man with atrial fibrillation presented to the emergency department with abdominal pain that had worsened over the course of 1 day. The patient had suffered a similar attack 6 months earlier and was diagnosed with mesenteric ischemia. He had received anticoagulant therapy since this first attack. Physical examination revealed mild pale conjunctiva, hypoactive bowel sounds, and mild muscle guarding over the lower abdomen without bleeding. Laboratory analysis revealed normal liver and rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…We have also used the SMI technique to aid in the diagnosis of intramural hematoma after an abdominal CT scan revealed intestinal wall thickening [ Figure 3 ] over a long section of the small intestine in a 77-year-old patient who had sought medical attention for acute abdominal pain. [ 3 ] In this case, SMI revealed that the thickened intestinal wall still had capillary blood flow [ Figure 4 ], allowing her physician to eliminate bowel ischemia as the etiology of her pain ([Figures 1 - 4 ] have been partially picked from the previous publication as noted in Reference 2 and 3). Since the patient had a history of anticoagulant use, the diagnosis of intramural hematoma of the intestine was confirmed by endoscopy [ Figure 5 ], and her symptoms improved after the patient stopped the use of anticoagulants.…”
mentioning
confidence: 97%
“…We have also used the SMI technique to aid in the diagnosis of intramural hematoma after an abdominal CT scan revealed intestinal wall thickening [ Figure 3 ] over a long section of the small intestine in a 77-year-old patient who had sought medical attention for acute abdominal pain. [ 3 ] In this case, SMI revealed that the thickened intestinal wall still had capillary blood flow [ Figure 4 ], allowing her physician to eliminate bowel ischemia as the etiology of her pain ([Figures 1 - 4 ] have been partially picked from the previous publication as noted in Reference 2 and 3). Since the patient had a history of anticoagulant use, the diagnosis of intramural hematoma of the intestine was confirmed by endoscopy [ Figure 5 ], and her symptoms improved after the patient stopped the use of anticoagulants.…”
mentioning
confidence: 97%